USER RESEARCH ON HOUSEHOLD FOOD WASTE AMONG URBAN RESIDENTS IN JAKARTA: UNDERSTANDING BEHAVIORS FOR UI UX DESIGN - Gumulya, Devanny; Alfiora, Catharina Carissa (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Indonesia is the second-largest producer of food waste globally, making it a significant issue that demands urgent attention. To address this problem, various technological tools, such as mobile apps, can help users track and manage their food consumption. Unfortunately, most existing apps are designed for Western contexts and are not well-suited to Indonesian households. Developing an effective app requires comprehensive user research. This study leverages the Food Consumption Management model and the Motivation, Ability, and Opportunity framework to identify key behaviors contributing to food waste at the household level. Given the exploratory nature of the problem, a mixed-methods approach was used, combining surveys and interviews from diverse household settings. The study identified five key challenges: impulsive shopping, knowledge gaps in food management, time constraints, family dynamics, and the motivation to save money. Based on these findings, the proposed app features include real-time notifications, AI-assited recipe suggestions, quick meal planning modes, collaborative tools for family use, and progress-tracking dashboards. Gamification is also suggested to enhance user engagement and promote sustainable behaviors. This study provides preliminary research on user behavior for UI UX App Design, so the app can offer features that effectively promote sustainable food habits in Indonesian households.